The Significance of The Syncretization of Naqshbandi Teachings with National and Universal Values in The Spiritual Heritage of Alisher Navoi - Markhabo Davlatovna Pardaeva (Scientific Trends, 2025)
The article examines the significance of the syncretization of Naqshbandi teachings with national and universal values in the spiritual heritage of Alisher Navoi. Special attention is given to the way Navoi integrated the ethical principles of the Naqshbandi order—such as humility, service, sincerity, and inner purification—with the cultural ideals of the Uzbek people and timeless human values. This synthesis, reflected in his philosophical and literary works, highlights the ability of spiritual traditions to transcend local boundaries and acquire universal relevance. The study emphasizes that Navoi’s heritage not only embodies national identity, but also serves as a bridge between Eastern and Western thought, tradition and modernity, individuality and universality. The conclusions point to the contemporary relevance of Navoi’s ideas in fostering intercultural dialogue, moral development, and the consolidation of humanistic values in the era of globalization.
Keywords: Alisher Navoi; Naqshbandi teachings; syncretization; national values; universal values; spiritual heritage; intercultural dialogue; humanism; philosophy of culture; Sufism.